Validação do manual saúde sexual e reprodutiva: métodos anticoncepcionais comportamentais para cegas - Oliveira, Mariana Gonçalves de (2016)
Blind women have low supply of educational material on health. accessible educational manual is possibility of teaching and learning by providing information on sexual and reproductive health with a focus on behavioral contraceptive methods. This study aimed to: Validate Assistive Technology for blind in Manual mode on behavioral contraceptive methods for health promotion. It is quasi-experimental research, developed in the city of Fortaleza in the state of Ceará in the period from February 2014 to September 2015. We used non-probability sample of convenience, content experts and blind women. Data collection was divided into two phases: Learning Assessment Instrument validation with experts and manual validation with blind women. It was built by the author and then validated by experts a Knowledge Assessment Tool (pre and post test). In the second stage, it applied the instrument (pretest) and delivery of the Manual for reading, then scheduled another meeting for application of this instrument (post-test) and return the manual. Data were organized in tables and graphs with absolute and relative frequencies. We used the Cronbach's coefficient alpha, the statistical the McNemar test, and the odds ratio McNemar test and the Wilcoxon marked positions. They were respecting the ethical and legal precepts. The study enrolled five experts and 48 blind women. Note that all the items of the instrument were considered well written and easy to understand; and by relevant experts. There was excellent agreement between the experts after analysis was considered highly significant (p <0.001), so suitable for data collection. Most participants (52%) had congenital blindness. The age ranged from 18 to 66 years, mean 35 ± 14 years, predominantly the range 18-29 years (42%). Predominated women with higher education (40%) and unmarried (56%). The mean score on the pretest and post-test in blind women with the type of blindness showed statistical significance in with acquired blindness (<0.001) and congenital (<0.001). Regarding the age group showed a statistical significance in average pre and post test of correct answers in the blind women aged 18 to 29 years (p = 0.002), 30 to 39 years (p = 0.001) and 40 or more years (p = 0.002). Regarding education, it was observed that the average of correct answers in the pre and post test showed statistical significance in blind women with high school (p <0.001) and higher education (p <0.001). Still, it was found that the average among women with primary education was below the group median values ​​(p = 0.056). The mean score before and after testing in blind women with regard to marital status showed statistical significance in single women (p <0.001) and married / stable (p <0.001). Thus, it was possible to measure learning and were confirmed good sized post-reading the manual adjustments, stressing that it represents excellent learning strategy, so the manual has been validated.